Alignment and theory in Corporate Real Estate alignment models - Heywood, Christopher; Arkesteijn, Monique (International Journal of Strategic Property Management, 2017)
This paper deepens the understanding of Corporate Real Estate (CRE) alignment through a meta-study of twenty existing alignment models. A qualitative hermeneutic method interpreted the models and their articles. This holistic analysis found alignment to be more complex and pluralistic than the individual models assumed. Four dimensions operating simultaneously were evident – a multi-valent relationship, multiple alignment forms, multiple cognitive objects to align and alignment in multiple directions. Alignment theorisation had positive and negative aspects. Positive is that good science was evident and had improved over time. Negative is that model theorisation had occurred mostly in isolation and was constrained by simplifications required to make modelling tractable. The research makes a meta-theoretical contribution through a more complete theorisation of CRE alignment as a phenomenon. This addresses a disordered sense to prior theory thereby representing a major conceptual improvement. A new alignment model is not proposed; rather through developed understanding a basis is provided to examine alignment in both theorisation and practice.